O Instituto Nacional do Livro e a institucionalização de organismos culturais no Estado Novo (1937-1945): planos, ideais e realizações - Silva, Suely Braga da (1992)
The foundation of the Instituto Nacional do Livro - INL - within the political and educational context of the 30’s and its performance until the end of the dictatorship of Estado Novo (1945). The debate established between the Escola Nova movement supporters and the catholic conservatives. The planning of the Plano nacional de Educação and the suggestion of an extra-school educational action. Political and financial difficulties in the first years of the INL. Objectives, scope and results reached by the Instituto through the study of its three sections: Publishing Section, Encyclopedia and Dictionary Section and Library Section. Analysis of the performance the Library Section in pursueing its major goal - to stimulate the organization and help the maintenance of public libraries all over Brazil - based on data of the 3.044 libraries which were registered at the Instituto between 1938 and 1945 on the purpose of benefitting from its program of book donation.